Distinct immunomodulation of bone marrow-derived dendritic cell responses to Lactobacillus plantarum WCFS1 by two different polysaccharides isolated from Lactobacillus rhamnosus LOCK 0900 - Górska, Sabina; Schwarzer, Martin; Jachymek, Wojciech; Srutkova, Dagmar; Brzozowska, Ewa; Kozakova, Hana; Gamian, Andrzej (Applied and environmental microbiology, 2014)
The structures of polysaccharides (PS) isolated from Lactobacillus rhamnosus LOCK 0900 and results from stimulation of mouse bone marrow-derived dendritic cells (BM-DC) and human embryonal kidney (HEK293) cells stably transfected with Toll-like receptors (TLR) upon exposure to these antigens were studied. L. rhamnosus LOCK 0900 produces PS that differ greatly in their structure. The polymer L900/2, with a high average molecular mass of 830 kDa, is a branched heteropolysaccharide with a unique repeating unit consisting of seven sugar residues and pyruvic acid, whereas L900/3 has a low average molecular mass of 18 kDa and contains a pentasaccharide repeating unit and phosphorus. Furthermore, we found that both described PS neither induce cytokine production and maturation of mouse BM-DC nor induce signaling through TLR2/TLR4 receptors. However, they differ profoundly in their abilities to modulate the BM-DC immune response to the well-characterized human isolate Lactobacillus plantarum WCFS1. Exposure to L900/2 enhanced interleukin-10 (IL-10) production induced by L. plantarum WCFS1, while in contrast, L900/3 enhanced the production of IL-12p70. We conclude that PS, probably due to their chemical features, are able to modulate the immune responses to third-party antigens. The ability to induce regulatory IL-10 by L900/2 opens up the possibility to use this PS in therapy of inflammatory conditions, such as inflammatory bowel disease, whereas L900/3 might be useful in reverting the antigen-dependent Th2-skewed immune responses in allergies.
Keywords: Lacticaseibacillus rhamnosus; konformace sacharidů; buňky kostní dřeně; Polysaccharides, Bacterial; Carbohydrate Conformation; Toll-Like Receptor 4; lidé; Mice, Inbred BALB C; Molecular Weight; probiotika; monosacharidy; cytokiny; toll-like receptor 2; bakteriální polysacharidy; Toll-Like Receptor 2; Humans; Monosaccharides; Magnetic Resonance Spectroscopy; Cytokines; molekulová hmotnost; HEK293 buňky; myši inbrední BALB C; zvířata; Dendritic Cells; Animals; Bone Marrow Cells; imunologické faktory; Immunologic Factors; toll-like receptor 4; dendritické buňky; magnetická rezonanční spektroskopie; HEK293 Cells; Probiotics